De la Provence aux Balkans : discours épilinguistiques autour d'un atlas sonore des langues régionales ou minoritaires d'Europe - Boula de Mareüil, Philippe; Courthiade, Marcel; Vernier, Frédéric (CCSD, 2023)
International audience To promote linguistic diversity, we propose to present a speaking atlas of regional or minority languages which, starting from Metropolitan France, has been extended to the French overseas territories, to languages without compact territory such as Rromani, as well as to other countries in the immediate vicinity of France. This online atlas <https://atlas.limsi.fr> allows visitors to listen to the same Aesop fable (and to read it) in over 900 versions. This work is the result of numerous field surveys and the development of an attractive interface. As confinement hardly lends itself to field linguistics, during the quarantine of 2020 we undertook to collect around forty translations of this fable, via the Internet, in minority languages/dialects of Europe.We will describe their mapping and we will focus on some of the endangered languages collected, from various linguistic areas: Romance (Occitan, Moeso-Romanian and Aromanian), Finno-Ugric (Sámi, Meänkieli and Kven), and Slavic (Ruthenian, Moravian and Bunjevac). We will see that these languages raise common, controversial questions, due to their obsolescence. The heterogeneity of these languages, almost consubstantial with their minority state, will thus fuel a purist, fixist and essentialist discourse: “we don’t say it like that” or, between two varieties of these languages, “they [the others] don’t speak like us”. Under these conditions, the writing of minority languages, which is crucial for their documentation and survival, raises important questions, which are shared by the languages selected here. Different solutions proposed will be discussed, which continue to be debated, in the Oc Gallo-Romance area (Provençal and Oriental Languedocien, from which we will start and which we will analyze in detail) as well as in the Balkans especially. Pour promouvoir la diversité linguistique, nous proposons de présenter un atlas sonore de langues régionales ou minoritaires qui, à partir de la France hexagonale, a été étendu aux ...